The impact of NAFTA on the United States - Burfisher, Mary E.; Robinson, Sherman; Thierfelder, Karen (American Economic Association, 2001)
We describe the main economic arguments posed for and against the North American Free Trade Agreement (NAFTA) during the U.S. policy debate. To evaluate these arguments, we analyze recent trade data and survey post-NAFTA studies. We find that both the U.S. and Mexico benefit from NAFTA, with much larger relative benefits for Mexico. NAFTA also has had little effect on the U.S. labor market. These results confirm the consensus opinion of economists at the time of the debate. Finally, studies find that trade creation greatly exceeds trade diversion in the region under NAFTA, especially in intermediate goods. -- Authors' Abstract